Facile preparation of uniform FeSe2 nanoparticles for PA/MR dual-modal imaging and photothermal cancer therapy. Issue 48 (25th November 2015) - Fu, Tingting; Chen, Yuyan; Hao, Jiali; Wang, Xiaoyong; Liu, Gang; Li, Yonggang; Liu, Zhuang; Cheng, Liang
Abstract : For the first time, we demonstrated that FeSe2 nanoparticles may have great potential as a safe, multi-functional theranostic agent for imaging guided photothermal treatment of cancer. Abstract : Recently, magnetic photothermal nanomaterials have emerged as a new class of bio-nanomaterials for application in cancer diagnosis and therapy. Hence, we developed a new kind of magnetic nanomaterials, iron diselenide (FeSe2 ) nanoparticles, for multimodal imaging-guided photothermal therapy (PTT) to improve the efficacy of cancer treatment. By controlling the reaction time and temperature, FeSe2 nanoparticles were synthesized by a simple solution-phase method. After modification with polyethylene glycol (PEG), the obtained FeSe2 -PEG nanoparticles showed high stability under various physiological conditions. FeSe2 -PEG could serve as a T 2-weighted magnetic resonance (MR) imaging contrast agent because of its strong superparamagnetic properties, with its r 2 relaxivity determined to be 133.38 mM −1 S −1, a value higher than that of the clinically used Feridex. On the other hand, with high absorbance in the near-infrared (NIR) region, FeSe2 -PEG also appeared to be a useful contrast agent for photoacoustic imaging (PA) as well as an effective photothermal agent for PTT cancer treatment, as demonstrated in our animal tumor model experiments. Moreover, long-term toxicity tests have proven that FeSe2 -PEG nanoparticles after systematic administration rendered no appreciable toxicity to the treated animals, and could be gradually excreted from the major organs of mice. Our work indicates that FeSe2 -PEG nanoparticles would be a new class of theranostic agents promising for application in bioimaging and cancer therapy.